THE ISLAMIC FACTOR IN THE NORTHERN CAUCASUS - MARZIEV, Ibrahim (CENTRAL ASIA AND THE CAUCASUS, 2005)
The role of Islam in North Caucasian politics has long been a topic of discussion in the academic, political, and journalist community. The term “the fault line” used by Prof. Huntington to describe the clash of civilizations looks tempting in the North Caucasian context. Indeed, it is an area with a high level of social and political tension and ethnic conflicts (more or less natural in the homeland of nearly 100 nationalities) rooted in economic and political inequality, unjust distribution of land, and an unwillingness to show justice when dealing with these evils. In addition, there are attempts to add religious hues to the already burning ethnic issues. Perestroika started Muslim renaissance in Russia; it was at that time that Islam moved into the sphere of politics. In 1990, Akhmad-qadi Akhtaev and the Kebedov brothers, among others (very popular as the leaders of “renovationist” Islam in Daghestan also known as Wahhabism), set up the Islamic Revival Party (IRP). Wahhabism is part of a wider movement called Salafism. We can paraphrase the formula “every Islamist is a Muslim, while not every Muslim is an Islamist” used by political scientist Igor Dobaev1 to say, “every Wahhabi can be described as a Salafi, but not all Salafis are Wahhabis.” The local Salafis concentrated on criticizing the Sufi Sheikhs for their complete loyalty to the secular state, which developed into conformism. In fact, they were also criticized by common Sufis for the fairly superficial nature of the process of re-Islamization limited to building new mosques and restoring holy places (ziyarats)—nothing was done to revive Tariqah as the method of mystic cognition.There is the opinion that in the Northern Caucasus, Wahhabism was promoted on foreign money, but we should bear in mind that no radical idea could have been accepted in the Caucasus in the absence of adequate local conditions. Soviet power destroyed the network of Islamic educational establishments: by the late 1980s, decades of repressions, anti-religious propaganda, and mosque closures wiped out the knowledge of Arabic to the extent that not all imams could independently study the necessary theological literature. Islam was no longer a religion—it had degenerated into a system of rituals and moral prescriptions. This gave rise to groups that called for the revival of “pure” Islam and detached themselves from “everyday” Islam. The youth alien to Sufi mysticism was very much attracted by Salafi rationalism.